Bioactive ent-isopimarane diterpenoids from Euphorbia neriifolia. (July 2020) - Li, Jian-Chun; Dai, Wei-Feng; Liu, Dan; Jiang, Ming-Yan; Zhang, Zhi-Jun; Chen, Xuan-Qin; Chen, Chin-Ho; Li, Rong-Tao; Li, Hong-Mei
Abstract: Twelve ent -isopimarane diterpenoids, including six undescribed ones, eupnerias J−O, were isolated from the stem barks of Euphorbia neriifolia L. Structurally, eupnerias J−M were the first examples of 18 (or 19)-norditerpenoid with ent -isopimarane skeleton from E. neriifolia . The absolute configuration of eupneria J was established based on the X-ray diffraction analysis and the experimental and calculated electronic circular dichroism (ECD), while the absolute configuration of eupnerias K–N were determined by the experimental and calculated ECD. In addition, the absolute configuration of the known compound, 3 β -hydroxysandaracopimaric acid, was determined by comparing its ECD spectrum with eupneria J, and renamed as eupneria P. Furthermore, eupneria J and eurifoloid H showed significant anti-HIV-1 activities with IC50 values of 0.31 and 6.70  μ g/mL, respectively, and ent -isopimara-8(14), 15-dien-3 β, 12 β -diol possessed obvious anti-influenza virus activity against A/Puerto Rico/8/1934, with an IC50 at 3.86  μ g/mL. Graphical abstract: Image 1 Highlights: Six undescribed ent -isopimarane diterpenoids were isolated from E. neriifolia. Eupnerias J-M possessed ent -18 (or 19)-nor-isopimarane diterpenoid skeleton. Eupneria J and eurifoloid H showed significant anti-HIV-1 activity. Ent -isopimara-8(14), 15-dien-3 β, 12 β -diol had obvious anti-influenza virus activity.